Evaluating dynamics of water yield and its driving forces in the Taihang Mountain Region, China - Bo Guo; Hui Yang; Chunyu Zhu; Ying Guo; Yuhan Zhao; Jiansheng Cao; Yanjun Shen (Ecological Indicators)
Water yield (WY) is a critical indicator of water availability, playing a significant role in sustaining ecosystem stability. Understanding the factors influencing water yield is crucial for effective regional water resource management and the long-term sustainability of ecosystems. However, the dynamics of water yield and the driving mechanisms in the Taihang Mountain Region (TMR), particularly the influence of extreme precipitation, remain insufficiently understood. In this study, we employed the InVEST model to analyze water yield dynamics across the TMR. We introduced an analytical framework that integrates detrending analysis with scenario-based simulation to investigate the contributions of climate change (CC) and land use and land cover change (LUCC) to water yield. Furthermore, we applied the optimal parameters-based geographical detector (OPGD) to examine the influence of precipitation characteristics on water yield. We found that water yield in the TMR exhibited a decreasing trend of −0.66 mm/yr from 1990 to 2020. Significant spatial heterogeneity was observed in water yield changes, with notable decreases predominantly distributed in the eastern slope of the TMR. CC and LUCC contributed 86.46 % and 13.54 % to water yield variation, respectively. Our findings revealed that changes in water yield in the TMR are strongly influenced by precipitation patterns, with precipitation trends and extreme precipitation serving as the primary drivers. Notably, in areas experiencing significant water yield decline, precipitation intensity plays a more dominant role than precipitation trends. Afforestation areas exhibited a significantly higher decline in water yield than non-afforestation regions from 1990 to 2020. These findings provide valuable insights for guiding afforestation projects in TMR.